Uso de história em quadrinhos como ferramenta de divulgação científica sobre a taxonomia da família Gesneriaceae - Silva, Matheus Felipe Ferreira (Universidade Federal de São Carlos, 2025)
Science communication plays a crucial role in democratizing knowledge, making scientific concepts accessible to diverse audiences through adapted language and formats. Comic books have emerged as an effective tool in this context, combining visual and textual elements to present complex ideas in an engaging and approachable manner. Botany, in particular, faces significant challenges in education and public awareness due to the phenomenon of "Botanical Imperception" — a general lack of interest in and recognition of the importance of plants. This study aims to develop educational material in the form of a comic book that illustrates the processes of an undergraduate research project in Botany. The content covers key methodological stages, fundamental concepts of taxonomy, and the research findings. To achieve this, a script was developed based on real research data, forming the foundation of a narrative that features characters representing researchers and their scientific investigation. The illustrations were initially hand-drawn, then scanned and digitally colored using illustration software. By integrating these techniques, the project seeks to enhance the understanding of scientific concepts and foster greater interest in botany, particularly among students and the general public. The final comic book 'A Botanical Journey' includes a cover and five more pages, containing about 30 panels.
Using comic books as a science communication tool for the taxonomy of the Gesneriaceae family
Keywords: Popularização da Ciência; Material Didático; Ensino de Botânica; Sistemática Vegetal; Popularization of Science; Didactic Material; Botany Teaching; Plant Systematics; CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL